Development of Supervision Based on Emotional Intelligence Model on Nursing Service Quality - Andayani, Evi; Fitryasari, Rizki; Sari, Dianis Wulan; Ayatulloh, Daviq; Priyantini, Diah (Indonesian Journal of Global Health Research, 2024)
The quality of nursing services in hospitals is related to the assessment of patient and family satisfaction, so supervision is needed to minimize the provision of less-than-optimal nursing services. Supervision is influenced by the emotional condition and intelligence of the supervisor. This research aims to develop a supervision based on emotional intelligence (EI) model for the quality of nursing services. The research consisted of two stages, namely stage 1 using an explanatory survey with a cross sectional approach. The population was 262 nurses at Blambangan Hospital, Banyuwangi Regency, r sample of 168 respondents was obtained through probability sampling with cluster random sampling. Data was collected using a questionnaire and analyzed using Partial Least Square (PLS). Stage 2 research is the preparation of a supervision based on EI module that refers to strategic issues obtained from the results of the first stage research, focus group discussions and expert consultations. There is a significant influence of individual factors (T=8.789), organizational factors (T=4.519), psychological factors (T=13.853), and work factors (T=3.517) on supervision based on EI. There is an influence of individual factors (T=11.703), organizational factors (T=5.012), psychological factors (T=9.008), and work factors (T=6.512) on the quality of nursing services. There is an influence of supervision based on EI (T= 3.224) on the quality of nursing services, as well as the arrangement of supervision based on EI modules to improve the quality of nursing services. The development of supervision based on EI which includes normative, formative and restorative can be an effort by the head of the room or supervisor to improve the quality of nursing services and it is important to pay attention to self-awareness, social awareness, self-management and relationship management.